Understanding Poverty : A Relational Approach - Seale, Elizabeth Kelley (Cambridge ; Hoboken, NJ : Polity, 2023)
People in poverty suffer daily under misconceptions about economic hardship and its causes. Providing the most comprehensive consideration to date of poverty in the United States, Elizabeth Sealse tackles how we think about issues of culture, behavior, and poverty, cutting straight to the heart of debates about social class. The book addresses tough questions, including how being poor affects individual behavior, and how we can make sense of that in a larger social and political context. The central premise is that to understand the behavior and lives of people in poverty, one must consider their relational context, especially relations of vulerability and the human need for dignity. Poverty is a social problem we should address as a society by changing social relations that, as a matter of course, cause unnecessary and immense suffering. To do so, we must directly confront our lack of regart for people in poverty by recognizing that they are in fact worthy of an effort to induce major social change. From back cover.
Includes bibliographical references (pages 189-221) and index.
Keywords: Poverty -- United States; Interpersonal relations -- United States; Poverty; United States -- Social conditions